Interaction of fructose with the glucose permease of the cyanobacterium Synechocystis sp. strain PCC 6803. - Flores, E (1986)
Fructose was bactericidal for the cyanobacterium Synechocystis sp. strain PCC 6803. Each of ten independently isolated fructose-resistant mutants had an alteration of the glucose transport system, measured as uptake of glucose or of 3-O-methyl-D-glucose. In the presence of the analog, the wild-type Synechocystis strain was protected against fructose. Two mutants altered in photoautotrophy were also isolated.